Usulan Perbaikan Tata Letak Fasilitas Lantai Produksi Dengan Metode Systematic Layout Planning (SLP) di PT DSS - Nurhidayat, Fajar (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2020)
The facility layout design is important in increasing company productivity. PT DSS is a construction company in the Sentul industrial area. Currently, the company wants to increase its production target to meet growing consumer demand. The current condition layout is not in accordance with the needs, which is indicated by the intersecting flow of the production process which causes the production time to be longer. The method used is to use the SLP Systematic Layout Planning method which functions to produce a layout design for production facilities that can minimize the total cost of material handling and minimize the distance between the PT DSS production rooms and so that there are no more intersecting production process flows. Based on the results of research and calculations with this method, the results of the improvement in the production layout of proposal 2 are better. The initial layout material handling distance is 32,934 meters with material transfer costs Rp. 2,424,579, and the proposed layout 2 is 18,783 meters apart with material handling costs of Rp. 1,630,896 and a savings of 32% is obtained from the initial layout.